2012
DOI: 10.1111/j.1749-4877.2011.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal effects on seed dispersal and seed predation of Musa acuminata in southern Yunnan, China

Abstract: Wild bananas are abundant in tropical areas and many ecologists have observed that the succession process is quicker following increased disturbance. This study was conducted to analyze animal-seed interactions and their effects on the seed fate of a wild banana species (Musa acuminata) in tropical southern Yunnan (China) through experiments considering spatial (site and habitat) and temporal (seasons) variation. The largest proportion of fruits (81%) was removed by frugivorous seed dispersers, especially by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Seed crop may have an important impact on seed survival and subsequent establishment [41], [43][44]. Our study indicated that seed fate and seed survival were different between plots, reflecting the spatial effects on seed dispersal and seed predation [45]. Previous studies have shown that scatter-hoarding and dispersal distances are enhanced during mast years compared with those during non-mast years (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…Seed crop may have an important impact on seed survival and subsequent establishment [41], [43][44]. Our study indicated that seed fate and seed survival were different between plots, reflecting the spatial effects on seed dispersal and seed predation [45]. Previous studies have shown that scatter-hoarding and dispersal distances are enhanced during mast years compared with those during non-mast years (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…Collecting mature seeds during collecting missions is much more challenging than from field germplasm collections. Collectors must access bunches before they are consumed and seeds are dispersed by birds and mammals [ 82 , 83 , 84 ]. Humans also harvest wild bananas for food, construction and artistry [ 37 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caching strategies may represent trade-offs between cache defense maximization and cache pilferage minimization (Hurly & Lourie 1997, Gerhardt 2005, Dally et al 2006). We acknowledge that many environmental factors may influence seed selection, seed removal and dispersal, and ultimately seed fates in the field (Hay & Fuller 1981, Holl & Lulow 1997, García-Castaño et al 2006, Meng et al 2012. Although the same-sized enclosures have been applied to investigate caching behavior of chipmunks and other rodent species , Chang et al 2009, Huang et al 2011, the seminatural enclosures cannot completely mimic the field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Seed size (Moles et al 2003, Xiao et al 2005a, Barcelos et al 2013, Capece et al 2013, handling time (Kaufman & Collier 1981), moisture content (Hulbert & Macmillen 1988), energy and soluble carbohydrates (Kelrick & MacMzhon 1985, Kerley & Erasmus 1991, Xiao et al 2005b), nutrients (Alexander et al 2001, Jansen & Forget 2001, Xiao et al 2006, secondary chemical compounds (e.g., tannins and other polyphenols - Steele et al 1993), seed coat thickness , Takechi et al 2009) as well as seed germination schedule have been identified to show influences on seed removal and dispersal. Apart from the influence of seed traits, environmental factors such as habitat qualities and seasonal variations show great impacts on seed removal and dispersal (Hulme 1997, Kollmann et al 1998, Wang et al 2000, Meng et al 2012.…”
Section: Introductionmentioning
confidence: 99%